MID-LIFE FALLS ARE ASSOCIATED WITH INCREASED RISK OF MORTALITY IN WOMEN. (11th November 2018) - Karvonen-Gutierrez, C; Ylitalo, K; Peng, M
Abstract: One-third of older adults fall annually, and falls are a leading cause of hospitalization, disability and mortality. The number of falls among mid-life adults (age 40–65 years) is comparable to estimates among older adults but it is unknown whether mid-life adults experience the same adverse consequences. Using data from the National Health and Nutrition Examination Survey (NHANES) III, we evaluated whether falling during mid-life was associated with an increased risk of mortality in the next 10 years. Participants (n=1, 295) were age 60–64.9 years of age. Using survey-weighted Cox regression models, hazard ratios (HR) and corresponding 95% confidence intervals (CI) of mortality among recurrent fallers (fell 2+ times) versus those that fell once or less were calculated. The 10-year mortality risk was 16.6% overall. Among those that died within 10 years, 20% were recurrent fallers as compared to only 5.5% among participants who survived. Recurrent fallers were more likely to be women and those with cardiovascular disease, stroke, and more prescription medications. Among women, in models adjusted for race/ethnicity, body mass index, smoking, education, cardiovascular disease, stroke, diabetes, cancer and number of medications, recurrent fallers had more than a 4-fold increased hazard of death in 10 years (HR=4.07, 95% CI: 1.99, 8.31). In parallel models among men, the association was much weaker and not statistically significant (HR=1.72, 95% CI 0.66, 4.50). Women experiencing multiple falls during the mid-life period may be at higher risk for premature mortality. Future work should examine the mechanisms underlying observed sex-specific risk of recurrent falls in women.